2019
DOI: 10.1186/s12951-019-0513-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel macrophage-mediated biomimetic delivery system with NIR-triggered release for prostate cancer therapy

Abstract: Background Macrophages with tumor-tropic migratory properties can serve as a cellular carrier to enhance the efficacy of anti neoplastic agents. However, limited drug loading (DL) and insufficient drug release at the tumor site remain the main obstacles in developing macrophage-based delivery systems. In this study, we constructed a biomimetic delivery system (BDS) by loading doxorubicin (DOX)-loaded reduced graphene oxide (rGO) into a mouse macrophage-like cell line (RAW264.7), hoping that the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 31 publications
(30 reference statements)
0
51
0
Order By: Relevance
“…It was found that the nano‐PTX‐loaded macrophages had better U87‐tumor‐cell inhibition than nano‐PTX alone. Similarly, macrophages loaded with SN38 NPs, [ 117 ] MSN NPs containing DOX, [ 113 ] rGO containing DOX, [ 118 ] and ironic oxide NPs [ 119 ] all showed excellent anti‐tumor ability against various animal tumor models.…”
Section: Engineering Macrophages For Drug Deliverymentioning
confidence: 99%
“…It was found that the nano‐PTX‐loaded macrophages had better U87‐tumor‐cell inhibition than nano‐PTX alone. Similarly, macrophages loaded with SN38 NPs, [ 117 ] MSN NPs containing DOX, [ 113 ] rGO containing DOX, [ 118 ] and ironic oxide NPs [ 119 ] all showed excellent anti‐tumor ability against various animal tumor models.…”
Section: Engineering Macrophages For Drug Deliverymentioning
confidence: 99%
“…Our previous studies [33,34] demonstrated that biomimetic nano-delivery systems mediated by macrophage or functional exosome are useful carriers for delivering chemotherapeutics or genes to tumor sites, via active targeting ability. Recently, cell membrane-based biomimetic NPs have received attention for potential drug delivery applications [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…This research suggests improved patient survival and high levels of intratumoral immune cell infiltrates [20]. Macrophages, which are circulating cells, are recommended by many studies for the treatment of tumors because the use of monocytes/macrophages provides several advantages compared to MSCs: they can be easily obtained from the patient, easily loaded into therapeutic drugs or nanoparticles, and reinjected into the bloodstream [5,11,21,22]. Additionally, macrophages naturally penetrate tumor tissue due to the fact that tumor-associated macrophages (TAM) are one of the most prominent components of tumor mass (up to 50%) [11,23].…”
Section: Introductionmentioning
confidence: 99%